2007
DOI: 10.1111/j.1939-1668.2006.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions: Debunking Television's Portrayal of Interior Design

Abstract: The authors argue that the popularity of design-related reality television shows may distort incoming students' perceptions of the interior design profession. I encourage you to read this Perspective and offer your thoughts in the Letters section of the next issue of theJourna1 of lnterior Design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…An important movement within the field of interior design is the emphasis on evidence-based design (Gurerin & Thompson, 2004;Waxman & Clemons, 2007). Evidenced based design is a term borrowed from the medical research community (Kopec, Sinclair, & Matthes, 2012) that recognizes the importance of including previous research in design efforts.…”
Section: Discussionmentioning
confidence: 99%
“…An important movement within the field of interior design is the emphasis on evidence-based design (Gurerin & Thompson, 2004;Waxman & Clemons, 2007). Evidenced based design is a term borrowed from the medical research community (Kopec, Sinclair, & Matthes, 2012) that recognizes the importance of including previous research in design efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Senior‐level students voiced the concern that these shows tarnished the image of interior designers. After watching a number of design‐related reality shows, Martin concluded that one of the myths perpetuated about the profession was that “anyone can be an interior designer” (cited in Waxman & Clemens, 2007, p. vii; see also Bowles, 2008). For those of us who entered the profession through the process of education, experience, and examination, the public's lack of knowledge of who we are and what we do is extremely frustrating.…”
Section: Role Of the Mediamentioning
confidence: 99%
“… There is much to be concerned about with reality television, not least of which is the portrayal of television hosts as interior designers who in fact often lack credentials (Waxman & Clemons, 2007). …”
mentioning
confidence: 99%